INVESTIGATION OF MICROSTRUCTURE AND THERMODYNAMIC PROPERTIES OF NITICU SHAPE MEMORY ALLOY AGED AT DIFFERENT TEMPERATURES - HAJI, AZAD IBRAHIM (Fırat Üniveristesi, 2021)
NiTiCu şekil hatırlamalı alaşımlar, mekanik ısıyla işlenebilir alaşımlardan biridir. Bu çalışmada, yüksek bakır içerikli NiTiCu alaşımlardaki mekanik, mikro yapı ve termodinamik gelişmeleri incelemek için ısıl işlem yapılmıştır. Yüzde doksan dokuz saflığa sahip üçlü NiTiCu alaşım metal tozları karıştırıldı. Daha sonra metal tozları, 10 MPa'lık bir basınçla preslendi. Ni30Ti50Cu20 at % alaşımı elde etmek için argon atmosferi altında ark eritme sistemi ile üretildiler. Daha sonra, alaşımın parçaları kesildi ve ısıl işlem süreci, bir saat boyunca 1073, 1123, 1173 ve 1223K sıcaklıklarda uygulandı. Yaşlandırma sürecinden sonra, tuzlu-buzlu su içinde ani soğutma işlemleri gerçekleştirildi. Isıl işlem görmüş alaşımların mikro yapısının, mekanik ve termodinamik özelliklerinin incelenmesi için DSC, SEM-EDS, Metalurjik mikroskop ve Vickers mikro sertliği gibi bazı cihazlar kullanılmıştır. Isıl işlem görmüş numuneler için diferansiyel tarama kalorimetresi (DSC) ölçümleri (10, 15, 20 ve 25K / dak) ısıtma/soğutma hızlarında gerçekleştirilmiştir. Ayrıca, ileri ve ters faz dönüşüm için aktivasyon enerjisi, entropi, Gibbs serbest enerjisi ve elastik enerji gibi bazı matematiksel hesaplamalar yapıldı. Aktivasyon enerjisini hesaplamak için üç farklı yöntem kullanıldı ve böylece sonuçlar tüm yöntemler için neredeyse aynı bulundu. Seçilen ölçüm aralığı için DSC eğrileri, austenit (B2) fazı ile martensit (B19) fazı arasında tek fazlı bir dönüşüm göstermiştir. Hesaplanan termodinamik parametreler, 1223K yaşlandırma sıcaklığına sahip alaşımın diğerlerine kıyasla maksimum bir değer olduğunu gösterir.Aynı zamanda yaşlandırma sıcaklığının artırılması, alaşımın kristalleşme boyutunda artışa neden olmuştur.

NiTiCu shape memory alloys are one of the mechanical heat-treatable alloys. In this study, heat treatment has been performed to investigate the mechanical, microstructure and thermodynamic improvements in high copper-content NiTiCu alloys. Metal powders ternary NiTiCu alloys with ninety-nine percent purity were mixed. Then, the metal powders were pressed to make pellets with a 10 MPa pressure. They were produced by an arc-melting system under the argon atmosphere to obtain Ni30Ti50Cu20 at. % alloy. After that, pieces of alloys were cut and the heat treatment process has been applied at1073, 1123, 1173, and 1223K for a single hour. After the aging process, the quenching operations were performed inside ice-salted water. For investigation of microstructure, mechanical and thermodynamic properties of the heat-treated alloys, some devices were used, including DSC, SEM-EDS, Metallurgical microscope, and Vickers microhardness. The differential scanning calorimetry (DSC) measurements were performed for the heat-treated specimens with heating/cooling speed rate of (10, 15, 20 and 25K/min). Besides some mathematical calculations, such as activation energy, entropy, Gibbs free energy, and elastic energy, were performed for the forward and/or reverse-phase transformation process. Three different methods were used to calculate activation energy, whereby, the results showed nearly the same values for all cases. For the chosen range of measurements, the DSC curves showed a single phase transformation between austenite (B2) phase and martensite (B19) phase. The calculated thermodynamic parameters were affected by the heat treatment such that the alloy with 1223K aging temperature showed a maximum value compared to the other counterparts. Also increasing the temperature of aging caused to increase in the crystallite size of the alloy.
Farklı sıcaklıklarda yaşlandırılan NiTiCu Şekil hafızalı alaşımın termodinamik ve mikroyapı özelliklerinin araştırılması
Keywords: Fizik ve Fizik Mühendisliği